Study on Molecular OPAY02-Scar Markers Related to Early Body Weight of New Yangzhou Chickens - Dai, G.J.; Wang, J.Y.; Olajide, O.; Li, Q.S.; Shen, H.; Xie, K.Z.; Wang, Z.Y.; Wu, S.L.; Gu, Y.P.; Zhang, G.X. (International Journal of Poultry Science, 2005)
In order to develop rapid and reliable SCAR markers linked to the QTL, to get better understood of orgin of New Yangzhou chickens, two bands of OPAY02 type marker have been cloned, sequenced and two pairs of primer were designed according to the DNA sequence of two bands of OPAY02 to amplify the SCAR-markers on 86 individuals randomly selected from New Yangzhou chickens. The results of comparing the two bands DNA sequence with red jungle fowl genomic DNA database showed that the large molecular size band is located on the 3rd chromosome, the sequence identities were 98% and 8 SNPs mutations were detected, they were at 195 (T→G), 316 (A→T), 538 (G→ A), 731 (T→A), 1147 (G→A), 1329 (T→C), 1927 (C→ T) and 2081 (C→T). On the other hand, the small molecular size band can`t be found in red jungle chicken genomic DNA database, speculated that the source of New Yangzhou Chickens may originate from not only red jungle fowl, but also other jungle fowls. SCAR -markers confirmed that the two bands of OPAY02 type marker can be applied to genetic analyses because of its stability and reliability. Genotype equilibrium test showed that New Yangzhou chickens are in equilibrium on the two bands loci, two bands of OPAY02 type marker selection will be in favor of New Yangzhou chickens body weight breeding.